Classification of entrepreneurial risks in order to define business-processes of the business owner - A. S. Kuksov (State University of Management, 2019)
Owned business management inevitably implies the availability of tools for its implementation. The set of tools for such management is effective, when it can be integrated into the overall system of business processes. The problem lies in the selection of those managerial business processes, where the participation of the owner is necessary. Justification of the definition of such business processes is possible on the basis of systematization and identification of the risks, that must be assumed by the business owner. In theory and practice of management, the focus is on the management of the organization, which is implemented by hired specialists-managers. The role of business owners is rarely seen as an independent activity. Meanwhile, the goals and the role of business owners are far from adequate to the goals and roles of managers. This circumstance makes the problem of ownership business management urgent. Currently, the terms “owner contro”l and “ownership management” are used in literary sources. These terms do not coincide in their meaning. Ownership management includes ownership control and occurs when the owner solves the problems of strategic development. If strategic development goals are not set for any reason, the owner remains to develop a system of ownership control over the current state of the business. Ownership business management should be built on the development and control of the organization's business processes. The owner can not physically control all business processes, and this is not necessary. There is a need to highlight those business processes, that he must control necessarily. In our opinion, the solution of this problem can be built on the basis of an appropriate classification of entrepreneurial risks.